Automatic waste sorting and trash bin capacity monitoring system using solar panels based on Internet of Things (IoT) - Arby, Syahroni; Hamdani (Journal of Industrial Automation and Electrical Engineering, 2024)
Waste management is one of the common issues faced by many cities worldwide. Many people dispose of waste carelessly, failing to separate different types of waste, leading to piled-up and scattered garbage. This problem is caused by a lack of public awareness about environmental preservation and the absence of quick access between garbage bins and waste collectors, resulting in waste accumulation. Based on these issues, a smart trash bin based on the Internet of Things was designed using NodeMCU ESP32 as its microcontroller. The bin lid operates automatically using an infrared sensor as an object detector and is equipped with a DFPlayer module that can produce sound. The waste separator uses three proximity sensors and a DHT22 sensor to differentiate between wet organic, dry organic, and inorganic metal and non-metal waste. In this study, a trash bin was also designed with an ultrasonic sensor to detect the bin’s capacity, and the data was then sent via the Blynk platform, allowing waste collectors to access it through a smartphone. From the test results, the three proximity sensors and the DHT22 sensor successfully differentiated between wet, dry, metal, and non-metal waste. The data obtained by the ultrasonic sensor was also successfully transmitted to the collectors via the Blynk application